Os fundamentos conceituais da teoria do conhecimento na teoria estética de Theodor W. Adorno : primado do objeto, autenticidade e belo natural na arte - Bezerra, Mateus Matos (2025)
This research aims to investigate the conceptual underpinnings of Adorno's "Aesthetic Theory" through the concepts of primacy of the object, authenticity, and natural beauty. This investigation will be carried out by analyzing commentators and Adorno's aesthetics, mainly works from his late period, which seek to find a connection between the moments that ground Theodor Adorno's philosophy. Adorno's aesthetic conception is materialist, consequently, art presents a truth content linked to the historical-social context in which artworks are embedded. The present research demonstrates how Adorno constructs his aesthetics to explain the artwork as an object of knowledge that expresses the truth. As we can see, the reality that Adorno presents is directly positioned so that society is expressed not only as a social affirmation but as a construct of knowledge that reveals what capitalist society seeks to conceal. Modern art stands as the true expression of the possible society and as a denunciation of the current society, through a sensitive and rational expression of society.